2017
DOI: 10.1038/srep41697
|View full text |Cite
|
Sign up to set email alerts
|

Platelet activation determines the severity of thrombocytopenia in dengue infection

Abstract: Thrombocytopenia is common in patients with dengue virus (DENV) infections. With a focus on understanding the possible mechanism of thrombocytopenia in DENV infections we described a direct correlation between activation and depletion of platelets in patients. Our data showed a sharp decrease in platelet counts at day 4 of fever in patients. The high DENV genome copies in platelets correlated directly with the elevated platelet activation along with increased binding of complement factor C3 and IgG on their su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
1
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(143 citation statements)
references
References 32 publications
8
130
1
4
Order By: Relevance
“…Here, A129 male mice were infected with 1 ϫ 10 3 PFU of a clinical isolate of DENV-2 (strain 05K3295), resulting in elevated viral loads in serum, spleen, liver, and brain, as observed in the vehicle-treated control group, consistent with previous reports ( Fig. 7A to D) (19,(21)(22)(23). Treatment with compound 10 (10 mg/kg, intraperitoneally [i.p.…”
Section: Zandi Et Al Antimicrobial Agents and Chemotherapysupporting
confidence: 90%
“…Here, A129 male mice were infected with 1 ϫ 10 3 PFU of a clinical isolate of DENV-2 (strain 05K3295), resulting in elevated viral loads in serum, spleen, liver, and brain, as observed in the vehicle-treated control group, consistent with previous reports ( Fig. 7A to D) (19,(21)(22)(23). Treatment with compound 10 (10 mg/kg, intraperitoneally [i.p.…”
Section: Zandi Et Al Antimicrobial Agents and Chemotherapysupporting
confidence: 90%
“…Numerous studies have shown that platelets and megakaryocytes can be infected in vitro and also that active infection of platelets has been shown to occur in patients with acute dengue . Such infection of platelets may lead to thrombocytopenia and cytokine production, and so potentially contribute to severe clinical disease …”
Section: Introductionmentioning
confidence: 99%
“…Migraine is normal to severe aching pain in head with symptoms of nausea, vomiting, sensitivity to sound (phonophobia), sensitivity to light (photophobia) and head movements. Migraines is one of the most frequently found pathologies of the central nervous system (CNS) which leads to decreased work productivity, performance and affect one Peron out of ten [50]. A new classification of migraines by the Headache Classification Committee of International Headache Society (IHS) in 2004 called "migraines with aura.'…”
Section: Ginger In Treatment Of Migrainementioning
confidence: 99%